Role of Magnetic Resonance Imaging in Unconscious Patients due to Diffuse Axonal Injury and Its Prognostic Value - Karthikeyan, Y. R.; Purohit, Devendra; Sinha, Virendra Deo (Indian Journal of Neurotrauma, 2017)
Aim To study the long-term prognostic value of early magnetic resonance imaging (MRI) in unconscious patients with traumatic brain injury with findings of NCCT of the brain suggestive of diffuse axonal injury (DAI).Background Studies addressing the correlation of MRI with the pattern and duration of loss of consciousness due to DAI are few. The utility of MRI in predicting the functional outcome has not been reported in the Indian population.Materials and Methods In patients with DAI, MRI sequences including T1, T2*GRE (gradient recall echo), fluid-attenuated inversion recovery (FLAIR), diffusion-weighted imaging (DWI), and susceptibility-weighted imaging (SWI) were obtained. Glasgow coma scale (GCS) and Glasgow outcome scale (GOS) scores were documented at admission, on discharge, and at 3 months.Results A total of 54 patients (53 males, 1 female) were included in the study. The mean age was 27 ± 11.7 years. The mean GCS score on admission and at follow-up were 9.14 ± 2.3 and 11.7 ± 2.3, respectively. The mean GOS score on discharge and at 3 months were 2.6 ± 0.8 and 3.18 ± 1.02, respectively. SWI sequence detected maximum number of lesions followed by GRE and DWI. Patients with lesions in brainstem and basal ganglia were found to have a less favorable outcome as assessed by GCS and GOS at 3 months. There was no correlation between the total lesion load and outcome at 3 months.Conclusion In patients with DAI, SWI was found to be the most sensitive MRI sequence detecting maximum number of lesions. Patients with lesions in the brainstem and basal ganglia appear to have longer duration of unconsciousness and poorer outcome at 3 months.
Keywords: diffuse axonal injury; magnetic resonance imaging; prognosis; traumatic brain injury